The epidemiology of obstructed labor and postpartum hemorrhages among women 20-49 years in the municipalities of Goiânia and Goianésia do Estado de Goiás in the period 2015 to 2020 - de Souza Olinto, Isadora; Cariolita Japiassu Moraes, Brenda; Deliberalli, Leticia; Mirian Alves Júnior, Mauro; Lima Arruda, Evilanna (Seven Editora, 2023)
Labor may be hampered by two main reasons: abnormalities in the fetus or anatomical irregularities present in the mother. While, with regard to hemorrhage: it is defined as abnormal blood extravasation and occurs in various situations. In the case of postpartum hemorrhage corresponds to excessive loss of blood after childbirth whose main cause may be uterine tonia. This fact is conducive to the death of women, since postpartum hemorrhage is the main cause of maternal mortality worldwide (Khan et al., 2006; Purwosunu et al., 2016). DOI: https://doi.org/10.56238/tfisdwv1-055